Anthropometric, strength, climbing and training characteristics that predict outdoor rock climbing performance - Ezzy, A. C.; Hagstrom, A. D.; Shorter, K. A.; Gray, A. J. (Journal of Australian Strength and Conditioning, 2018)
The aim of this study was to examine anthropometric, strength, endurance, climbing and training characteristics of sport climbers to better understand how these components influence outdoor red-point performance. Twenty males (age 29.3 ± 5.8 years) and ten females (age 29.5 ± 2.7 years), with a self-reported red-point ability ranging from 18 to 34 on the Ewbank scale, took part in the study. Anthropometric, strength and endurance, as well as climbing and training parameters were assessed and compared to self-reported outdoor red-point performance. Using regression analysis, it was shown that 52.8% of the variance in outdoor red-point performance could be accounted for by relative crimp strength (30.3%) and outdoor climbing time (22.5%). A number of other experiences, strength and training characteristics also demonstrated association with red-point ability. These included climbing experience (r = 0.466 P = 0.014), starting age (r = -0.662 P < 0.000), weekly finger strength training (r = 0.609 P = 0.001), weekly finger endurance training (r = 0.485 P = 0.010), weekly upper arm training (RP: r = 0.394 P = 0.042), relative pinch strength (r = 0.442 P = 0.021) and relative grip strength (r = 0.385 P = 0.047). Based on these findings, it was concluded that athletes and coaches looking to improve outdoor performance should prioritise the development of finger strength and progress total outdoor climbing time towards 14 hours/week.